Peningkatan Kualitas Pelayanan Peningkatan Kualitas Pelayanan Surat Perjalanan Republik Indonesia Di Kantor Imigrasi Kelas I Khusu TPI Ngurah Rai: Peningkatan Kualitas Pelayanan - Sari, Dwi Selvita; Putri Prawitasari , Putu (J-Dinamika : Jurnal Pengabdian Masyarakat, 2023)
Public services aim to provide satisfaction to the community where these services can be in accordance with the wishes of the community. It can be concluded that quality public service or what can be called excellent service is making every effort to prepare or assist government officials in various forms of affairs to fulfill community needs and expectations. When examined from existing human resources, problems in service that can occur are always related to employee ethics and abilities. If the problems are viewed from an institutional perspective, the problems are in agencies that lack coordination and are convoluted. Excellent service can be achieved if the quality of the service provided by the service provider exceeds the expectations or expectations of service users or service recipients. There are various kinds of services immigration services provided by the Directorate General of Immigration, one of which is the provision of passport services for Indonesian Citizens. The increasing demand for passport applications for Indonesian citizens, the Directorate General of Immigration must always pay attention to the quality of services provided to the public to prevent complaints or complaints from recipients of public services. There are 4 (four) steps and strategies in an effort to improve the quality of passport services: increasing employee competency in public services, meeting community needs, setting service standards and standard operating procedures, and building a culture of excellent service.